KESEIMBANGAN ANTARA INVESTASI DAN HAK MASYARAKAT ADAT KENEGERIAN PANGEAN (STUDI KASUS PADA PT. RIAU ANDALAN PULP AND PAPER DI KABUPATEN KUANTAN SINGINGI) - Elfikri, Moh. Zaky; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Investment for a country is a necessity or a necessity, because investmentis one of the driving forces of the economy so that a country can encourage itseconomic development in line with the demands of the development of its society.Investment in a country will be able to take place well and be beneficial to thecountry and its people, when the state is able to establish investment policies inaccordance with the constitutional mandate and the role of investors who applythe basic principles of investment balance for society. Investment policies musthave a strong and clear philosophical and legal basis. Investment policy is like aray of light in which direction to go and at the same time the road to be followedthat leads to balance for the community.This type of research can be classified into the type of sociologicaljuridical research. With the research location in Pangean sub-district, KuantanSingingi Regency. The population and sample are parties related to the problemunder study. This study used primary data sources and secondary data and datacollection techniques were carried out by means of interviews and literaturereview.The results of research conducted by the author are on conflicts betweencommunities in Pangean within the PT concession area. Riau Andalan Pulp andPaper is located in Baserah Estate, Logas Tanah Darat District, causing aninvestment imbalance felt by the community in PT. Riau Mainstay Pulp andPaper. Therefore, in this discussion the author examines the investments made byPT. Riau Andalan Pulp and Paper has implemented the provisions and created aninvestment balance that is based on justice, thereby creating a prosperous societywith a company that coexists with the community.Keywords: Keseimbangan Investasi, Konflik, Hutan Tanaman Industri (HTI)